Friday

April 18, 2014

April 18, 2014

Posted by **CYNTHIA** on Thursday, November 20, 2008 at 8:39pm.

- trig -
**drwls**, Thursday, November 20, 2008 at 8:46pmcot^2x - csc^2x

= (cos^2x -1)/sin^2x

= -sin^2x/sin^2x = -1

**Related Questions**

trig - simplify the expression. (sin^2x+cos^2x) - (csc^2x-cot^2x)

trig - prove: cos*2x=csc*2x-2/csc*2x

trig - csc^2x secx/sec^2x+csc^2x

trig - simplify the expression. cos^2x+sin^2x/cot^2x-csc^2x

math - how do i solve this using trig identities? 2 csc^2x = 3 cot^2x-1

trig - simplify (sec^2x + csc^2x) - (tan^x +cot^2x) to either a constant or a ...

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

precalculus - 1.csc^2x-1/csc^2x=cos^2x 2.1/1-cosx+1/1+cosx=2csc^2x 3.sinxcosy+...

Calculus - Find the derivative of y=cot³(1-2x)² y'=3[cot(1-2x)²]² (-csc²(1-2x...

math - Simplify sin^2x+cos^2x+sec^2x -tan^2x+csc^2x-cot^2x